CGIAR’s role in digital extension services - Kropff, Wietske; Jiménez, Daniel; Molero, Anabel; Smith, Georgina; Mehrabi, Zia; Megan, Mazelle; Koo, Jawoo; Reynolds, Matthew P.; Ramírez Villegas, Julián Armando; Rupavatharam, Srikant; Etten, Jacob van; Ortíz Crespo, Berta; et al. (Bioversity International and the International Center for Tropical Agriculture, 2021)
CGIAR’s digital extension services bridge the gap between the development and the adoption of new climate change adaptation strategies. These services include new ways to disperse information on rainfed systems of agriculture, nutrition, pest control, new crop varieties, crop management practices, and more.